PETROLOGY AND PROVENANCE STUDY OF THE QUATERNARY CLASTIC SEDIMENTS FROM HERSO KILKIS (MACEDONIA, GREECE) - Georgiadis, I. K.; Tsirambides, A.; Kassoli-Fournaraki, A.; Trontsios, G. (Bulletin of the Geological Society of Greece, 2007)
The sediments analysed are generally coarse grained, sand gravels to gravel sands. The silt and clay content of the samples is low and their textural study revealed a fluvial deposition environment. The amounts of quartz, feldspars and lithic fragments range from 33% to 56%, 8% to 18% and 28% to 52%, respectively. The samples studied may be classified as garnet-mica bearing litharenites. Quartz, plagioclases and micas are the predominant constituents. Detritai calcite and pyroxenes are present in small amounts. The samples are texturally and mineralogically immature. Detailed polarized microscopy revealed the presence of garnet, staurolite, kyanite, zoisite, routile, epidote, zircon, apatite and tourmaline, as well as of opaque minerals. These accessory minerals are considered indexes of metamorphic provenance. Geochemically the samples are classified as sublitharenites and subarkoses, all being rich in Si02- The overall percentages of quartz, feldspars and rock fragments designate intense physical weathering and rapid transport and deposition in the Herso Basin which is part of a passive continental margin (recycled orogen).